Hydrothermal synthesis of nanosized anatase TiO2: photocatalytic activity. (15th February 2012) - Jesty, Thomas; Reddy, M.L.P.
Phase–pure anatase TiO2 nanocrystallites (620 nm) were synthesised from amorphous titania by hydrothermal process under relatively low temperatures (413453 K) in the presence of water. The precursor used for the hydrothermal synthesis was obtained by the precipitation stripping of the TiCl4 loaded organic solvent (tributylphosphate = TBP). TiCl4 was selectively extracted from the synthetic waste chloride liquors of titania industry by solvent extraction using TBP in kerosene as an extractant. The synthesised anatase TiO2 powders were characterised by XRD, SEM, IR and BET surface area. The influence of hydrothermal treatment conditions on the formation features, phase composition, particle size, morphology and properties of the products were investigated and discussed. The fact that the nucleation of anatase was accelerated by the presence of water suggested that water bonding with the surfaces of the primary particles of the amorphous titania forces the TiO6 octahedra units to rearrange to the anatase structure and acts as a catalyst for the structural rearrangement. The crystal growth of TiO2 to phase–pure anatase was proposed to proceed by face–sharing process through dissolution–precipitation of the dissolved TiO6 octahedra from the amorphous phase. It is evident from the XRD patterns that neither rutile nor brookite phases are present in the hydrothermally synthesised anatase TiO2 powders. Application of these nonocrystallites as photocatalyst was evaluated by photocatalytic degradation of methyl orange in water. The photocatalytic activity of anatase TiO2 was also compared with that of commercial photocatalysts, Hombikat UV 100 and Degussa P25.